Bugs for breakfast food and culture - Schrank, Jeffrey; Learning seed (Lake Zurich, Ill. : Learning Seed, 2001)
Multicultural look at how we eat. Illustrates that how we view food is learned. Explains that there are no universal food customs nor dietary restrictions. What one refuses to eat is a symbol of social identity
Title from title screen
Keywords: Food habits -- Cross-cultural studies; Food -- Cross-cultural studies; Food preferences -- Cross-cultural studies; Food -- Research; Nutrition